MORPHOLOGICAL INTERFERENCE ON STUDENTS' WRITING AT THE ELEVENTH GRADE OF MAN KOTA PALANGKA RAYA - Ikrimah, Ikrimah; Asi, Natalina (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2024)
Interference is defined as the divergence from the norm of language usage that occurs as a result of multilingualism with regard to one or more other languages. Interference occurs when students are studying both the intended language and their first language in the same time. The incapacity of a person who is bilingual to differentiate between the components of the two languages that they are fluent in will lead to a successful error that is known as morphologicalÂ interference. This occurrence also happens in MAN Kota Palangka Raya. This research was conducted to discover the various sorts of morphological interference created by the students at the eleventh grade of MAN Kota Palangka Raya in their English writing. The qualitative technique was used to analyse the data gathered for this research. The subjects were the students from XI MIPA 1 that consists of 34 students. In order to obtain the information, the researcher split the class into 7 groups, and each of those groups was given the assignment of writing an explanation text in English. There were 6 types of morphological interference: indefinite article, possessive, plural marker, simple past, past participle, and comparative adjective/adverb. The result showed that there were forty number of features that point to morphological interference. The dominant types that the students mostly errors in writing their Explanation Text in English was Past Participle. Followed by Plural Marker. Meanwhile Possessive has a small amount of errors, and students did not do many mistakes in writing the Indefinite Article.